A cross-sectional analysis of patient characteristics and practice patterns in the management of bipolar disorder across Turkey - YANARTAŞ, ÖMER (CUMHURIYET UNIV TIP FAK PSIKIYATRI ANABILIM DALI, 2014)
Objective: Bipolar disorder (BD) is one of the leading causes of disability among medical and psychiatric disorders associated with prevalent, chronic, severe and highly disabling characteristics. This study was designed to identify clinical characteristics and practice patterns in the management of outpatients with BD across Turkey. Method: This multi-center cross-sectional study involving 1001 patients diagnosed with using DSM-IV criteria was conducted prospectively at 31 outpatient psychiatry clinics for 12 months. Patient demographics, clinical features, family history, comorbid psychiatric disorders, and the treatment modalities were assessed by means of semistructured questionnaire. Results: Age at the onset of symptoms was 26.7 +/- 9.8 years, age at diagnosis was 28.9 +/- 10.4 years, and the time interval between them was 2.2 +/- 4.7 years. Misdiagnosis prior to current diagnosis was evident in 40.3% of bipolar patients. The most common type of first episode was mania (57.1%) and depression (34.5%). Comorbid psychiatric illness was identified in 12.0% of patients. Only 10% of patients were receiving monotherapy. The most commonly prescribed drugs for depressive, manic and mixed episodes were lithium, sodium valproate and quetiapine, respectively. Conclusion: The time interval between onset of symptoms and the initial diagnosis in Turkish sample was quite shorter than reported in the literature. The misdiagnosis rate in the present study and recent studies were similar. A low comorbidity rate appears to indicate a lower prevalence of comorbid disorders in BD in Turkish sample. Lithium, sodium valproate and atypical antipsychotics were more commonly used drugs in the treatment of BD in Turkey.
Keywords: clinical practice pattern; bipolar disorder; disease management; medical practice; Turkey; PERSONALITY-DISORDERS; DEPRESSION; MOOD; COMORBIDITY; MANIA